FACTOR RELATED TO THE SELECTION OF IUD CONTRACEPTION WOMEN METHOD IN THE WORK AREA OF TARUB COMMUNITY HEALTH CENTER - Rose Nur Hudhariani; Dyah Ayu Wulandari; Fauziah Winda Gurnita; Ratna Nur Pahaeni (Universitas Karya Husada Semarang, 2025)
Background: The main problem faced in Indonesia is high population growth rate, so there is a government program, namely Family Planning, to space pregnancies using contraceptive methods and create economic and social prosperity. However, there are factors that cause the Family Planning Program to not be optimal, some of which are the level of knowledge, age, education and husband's support. The aim of the study was to examine factors related to the choice of IUD contraceptive method among women of childbearing age.Method: This research is quantitative with correlative descriptive of cross sectional approach. The sample was 52 respondents using cluster sampling technique. Research instrument used factors related quisonaire. Result: There was a relationship between the level of knowledge (p-value 0.016) and husband's support (p-value 0.009) with the choice of IUD contraception method, but there was no relationship between age (p-value 0.888) and maternal education (p-value 0.